THE EFFECT OF TAX COMPLIANCE AND TAX AVOIDANCE ON DEFENDER'S BUSINESS STRATEGY IN COMPANIES LISTED ON LQ 45 ON THE INDONESIA STOCK EXCHANGE PERIOD 2016-2019 - Fransiska Theresia; Meco Sitardja; Fery Wijaya; Bambang Setiono (INDONESIAN JOURNAL OF ACCOUNTING AND GOVERNANCE, 2022)
The main purpose of the research is to analyze tax compliance dan tax avoidance on defender business strategy. This research was a quantitative descriptive research method. The sampel used in this research is a secondary data of LQ 45 on the periode 2016 to 2019, and based on purposive sampling method was obtained 23 companies. Variabel tax compliance and defender business strategy using variabel dummy. Variabel tax avoidance using CETR proxy. The data in this research was processed using SPSS (Statistical Package for Social Sciences) with Logistic Linear Regression method. This research shows that tax compliance have a significant influence to the defender business strategy and tax avoidance do not have influence to the defender business strategy